Claws and Fangs of Neoliberalism - Rômulo Carvalho Cristaldo (Monções, 2022)
The main objective of this essay is to analyse neoliberalism as an alternative for political administration. According to a theory developed in Brazil, political administration encompasses both macro- and micromanagement principles to represent the interests and agenda of a social class, or some fraction of it. The main findings are that the neoliberal rationale and its management principles—efficiency, accountability, performance, and competition—are employed to reprogramme entire societies to transfer wealth to rentier capital. That is why wherever it takes root, neoliberalism brings unemployment, impoverishment, economic instability, exhaustion of natural resources, and income inequality.